Internal corporate governance and the use of IPO over-financing: Evidence from China - Xin Xu; Yun Xia (China Journal of Accounting Research, 2012)
In this paper, we describe how Shenzhen A-share listed companies used funds raised in over-financed IPOs during the 2006-2010 period. In exploring the relationship between internal corporate governance and the use of funds raised in over-financed IPOs, we find that the use of such funds to engage in severe over-investment behavior is prevalent among listed companies. Reasonable internal corporate governance mechanisms can effectively alleviate over-investment problems listed companies encounter in using funds raised in over-financed IPOs. However, the same individual serving as both chairman and CEO leads to funds raised in over-financed IPOs being over-invested. Moreover, executives driven by high levels of monetary compensation are more likely to use funds raised in such IPOs to engage in over-investment. We find that improving the balance of power between shareholders will help alleviate the over-investment of excess IPO funds. In addition, the over-investment problem is less severe in state-controlled listed companies than in their non-state-controlled listed counterparts. This study provides policy recommendations for Chinese securities regulators to ensure listed companies use funds raised in over-financed IPOs both rationally and effectively.
Keywords: G10; G31; G38; 650; Internal corporate governance; IPO over-financing; Over-investment; Non-capital investment